Biochemical characterization of Arabidopsis thaliana DNA polymerase (Sn s role in the oxidative DNA damage bypass. - Amoroso, Alessandra; Conica, Lorenzo; Longoni, Paolo; Crespan, Emmanuele; Cella, Rino.; Maga, Giovanni (2009)
As obliged phototropic organisms, plants are continuously exposed to high level of reactive oxygen ,species (ROS), generated within the ceII as a result of the exposure to biotic stresses. sunlight and metabolic activity. The most frequent DNA oxidation damage. generated by ROS is the 7,8-dihydro-8 oxo-guanine (8-oxo-G) adduct, When present in the replicating DNA strand, this lesion is highly mutagenic, leading to the insertion by the replicative DNA polymerases (pols) of an adenine in place of the correct cytosine. Here we present the first characterization of an error-free mechanism for 8-oxo-G bypass operating in crude extracts of Arabidopsis thaliana. For the first time, our results show that, similarly to what observed in mammalian cells. plant cells prossess an efficient pathway for faithful translesion synthesis of oxidative DNA lesions.
Includes references.
1
Keywords: Arabidopsis thaliana; DNA polymerases; DNA damage; Oxidative stress; Genetic translation